Variants of CEP68 gene are associated with acute urticaria/angioedema induced by multiple non-steroidal anti-inflammatory drugs. - José Antonio Cornejo-García (Public Library of Science (PLoS), 2014)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the most consumed drugs worldwide because of their efficacy and utility in the treatment of pain and inflammatory diseases. However, they are also responsible for an important number of adverse effects including hypersensitivity reactions. The most important group of these reactions is triggered by non-immunological, pharmacological mechanisms catalogued under the denomination of cross-intolerance (CRI), with acute urticaria/angioedema induced by multiple NSAIDs (MNSAID-UA) the most frequently associated clinical entity. A recent genome-wide association study identified the gene encoding the centrosomal protein of 68 KDa (CEP68) as the major locus associated with aspirin intolerance susceptibility in asthmatics. In this study, we aimed to assess the role of this locus in susceptibility to CRI to NSAIDs by examining 53 common gene variants in a total of 635 patients that were classified as MNSAID-UA (n = 399), airway exacerbations (n = 110) or blended pattern (n = 126), and 425 controls. We found in the MNSAID-UA group a number of variants (17) associated (lowest p-value = 1.13 × 10(-6)), including the non-synonymous Gly74Ser variant (rs7572857) previously associated with aspirin intolerance susceptibility in asthmatics. Although not being significant in the context of multiple testing, eight of these variants were also associated with exacerbated respiratory disease or blended reactions. Our results suggest that CEP68 gene variants may play an important role in MNSAID-UA susceptibility and, despite the different regulatory mechanisms involved depending on the specific affected organ, in the development of hypersensitivity reactions to NSAIDs.